2019
DOI: 10.1016/j.physbeh.2019.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride related changes in behavioral outcomes may relate to increased serotonin

Abstract: Fluoride ingestion has been linked to changes in behavior in mice and rats, related to dose, sex of the animal, and the timing of exposure. Previous studies have shown the behavior of female rats to be most affected by postnatal fluoride exposure, and in this study we determined the effects of postnatal fluoride exposure on anxiety related behavior and serotonin. Mice given 50 ppm fluoride in drinking water had increased entries in the open arms of the elevated plus maze, suggesting reduced anxiety. Both perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…The results confirmed the enzymatic mechanism for melatonin deficit in ASD in the pineal gland as well as in the gut and platelets of patients [45]. In a cohort of children drinking water containing 2.5 ppm F, serum serotonin was also increased as compared to controls [46].…”
Section: Fluoride-induced Asd Symptomssupporting
confidence: 66%
“…The results confirmed the enzymatic mechanism for melatonin deficit in ASD in the pineal gland as well as in the gut and platelets of patients [45]. In a cohort of children drinking water containing 2.5 ppm F, serum serotonin was also increased as compared to controls [46].…”
Section: Fluoride-induced Asd Symptomssupporting
confidence: 66%
“…Over time, fluoride-exposed mice may exhibit increased serotonin levels compared to non-exposed mice. Mice that have been exposed to fluoride have been shown to exhibit increased serotonin and brain fluoride levels at multiple time points following the exposure [ 46 ]. Serotonin (5-hydroxytryptamine [5-HT]) is a neurotransmitter that when present in the brain at inadequate levels, is heavily implicated in the development of depression and anxiety [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the impact of this chemical on mental health has been studied less widely. Various research studies have looked at depression, anxiety, and stress in rats and mice due to fluoride exposure [ 39 , 40 , 42 , 44 , 45 , 46 ]. However, there is currently only one human-based study [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…[127,128]. Serum serotonin was also increased in a cohort of healthy children drinking water containing 2.5 ppm fluoride, as compared to controls [102,129].…”
Section: Sleepmentioning
confidence: 85%
“…Insomnia and sleep disorders occur in 50-80% of ASD patients [125,126]. The disruption of the serotonin-N-acetyl serotonin-melatonin pathway has been found in a group of 278 patients with ASD [127][128][129]. Pagan et al suggested the levels of plasma melatonin, whole-blood serotonin, and platelet N-acetyl serotonin as biomarkers for ASD.…”
Section: Sleepmentioning
confidence: 99%